Open-Label Study To Evaluate the Single-Dose Pharmacokinetics, Safety, and Tolerability of Doripenem in Infants Less than 12 Weeks in Chronological Age - Cirillo, Iolanda (Antimicrob Agents Chemother, 2015)
Doripenem, a parenteral carbapenem with broad-spectrum activity against aerobic Gram-negative and Gram-positive and anaerobic pathogens, is currently approved for use in adults in the United States and European Union. Single-dose doripenem pharmacokinetics in 52 infants <12 weeks in chronological age were investigated in this phase 1 study. Hospitalized, medically stable infants <12 weeks in chronological age were stratified into 6 groups based on chronological and gestational age designed to reflect increasing renal maturation and decreasing volume of distribution (V(z)) for β-lactam antimicrobials during the first 3 months of life. Subjects received single-dose doripenem (5 mg/kg of body weight for <8 weeks and 8 mg/kg for ≥8 weeks in chronological age) administered intravenously over 1 h. Plasma samples were obtained immediately before the end of the infusion and 1.5, 3, and 7 h after the start of the infusion. Urine was obtained by indwelling catheter during the 8 h following infusion. Doripenem showed linear pharmacokinetics across the 6 age groups. Neonates (<4 weeks in chronological age) had increased mean exposure (area under the plasma concentration-time curve from time zero to infinite time [AUC(∞)], 45.7 versus 32.4 μg · h/ml), longer elimination half-life (2.98 versus 1.79 h), and lower clearance (2.03 versus 3.03 ml/min/kg) compared with infants >4 weeks. Mean V(z) was highest in subjects with the earliest gestational age (<32 weeks): 0.564 liter/kg for neonates and 0.548 liter/kg for infants. Single-dose pharmacokinetics of doripenem administered as a 1-hour infusion in term and preterm infants <12 weeks in chronological age were similar to what has been observed in neonates and very young infants with other carbapenems. Single-dose doripenem was generally safe and well tolerated. (This study has been registered with ClinicalTrials.gov under registration no. NCT01381848 and with EudraCT under registration no. 2009-014387-20.)